Estudo do mecanismo de transferência horizontal da sequência de inserção IS1245, específica de Mycobacterium avium, para Mycobacterium kansasii - Rabello, Michelle Christiane da Silva [UNIFESP] (2009)
Mycobacterium avium and Mycobacterium kansasii are non-tuberculous mycobacteria frequently isolated in infections from HIV positive patients. In a previous study from our laboratory, a mixed culture of M. avium and M. kansasii from a bone marrow isolate of an HIV positive patient was studied. The analysis of isolated colonies allowed the detection of the insertion sequence IS1245, specific from M. avium, in M. kansasii. The presence of this element in M. kansasii was confirmed by PCR-IS1245, RFLP-IS1245 and sequencing. The objective of this study was to investigate the mechanism of transference of the IS1245 to M. kansasii. A band of approximately 100 kb was detected by PFGE in colonies of M. avium and M. kansasii from this mixed culture. Tests of mobility of this DNA band in PFGE gels, in different running conditions, and tests with exonucleases and topoisomerase I demonstrated that this band was a linear plasmid (pMA100) with proteins covalently linked to the 5’ ends. These findings led to the hypothesis that the pMA100 plasmid was responsible for the natural transference of the IS1245 element from M. avium to M. kansasii by conjugation. Experiments performed in vitro reproduced the conjugation event, not only with the M. kansasii strain from the mixed culture, but also with other two unrelated M. kansasii strains. The insertion sequence was stably maintained in the M. kansasii genome after 10 subcultures and its replicative transposition in M. kansasii was also observed. For the first time the natural horizontal gene transfer between different species of mycobacteria has been demonstrated.